2016
DOI: 10.1038/srep36188
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin-like 4 is critical for the maintenance of neural progenitor cells in dorsal midbrain of zebrafish larvae

Abstract: A delicate balance between proliferating and differentiating signals is necessary to ensure proper growth and neuronal specification. By studying the developing zebrafish brain, we observed a specific and dynamic expression of a microtubule destabilizer gene, stathmin-like 4 (stmn4), in the dorsal midbrain region. The expression of stmn4 was mutually exclusive to a pan-neuronal marker, elavl3 that indicates its role in regulating neurogenesis. We showed the knockdown or overexpression of stmn4 resulted in prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…Similar compensatory inconsistency was found in stmn4 mutants, which had a low (< 10%) portion of embryos showing similar phenotype to stmn4 morphants. Interestingly, the authors found that stmn1b was upregulated to compensate in stmn4△5 but not stmn4△4 mutants [56]. In our study, we observed that in response to klf8 deficiency, klf12b , a member of a subgroup of KLF family with a CtBP interaction site, was induced to compensate for the loss of klf8 .…”
Section: Discussionsupporting
confidence: 46%
“…Similar compensatory inconsistency was found in stmn4 mutants, which had a low (< 10%) portion of embryos showing similar phenotype to stmn4 morphants. Interestingly, the authors found that stmn1b was upregulated to compensate in stmn4△5 but not stmn4△4 mutants [56]. In our study, we observed that in response to klf8 deficiency, klf12b , a member of a subgroup of KLF family with a CtBP interaction site, was induced to compensate for the loss of klf8 .…”
Section: Discussionsupporting
confidence: 46%
“…Among them, 9 genes including Stmn4 , L1cam , Tenm4 , Clca3b , Gzme , Mmp10 , Igfbp2 , Creb5 and Slc14a1 were significantly down-regulated in WT cells but significantly up-regulated in PPARγ/+ cells from 0d to 5d. In zebrafish study, the functional analysis of stathmin-like 4 ( Stmn4 ) had shown its essential roles in the maintenance of neural progenitor cells, whose expression was revealed to be enriched in the diencephalon in situ hybridization analysis 18 , 19 . STMN4 gene has been also reported to be involved in neuroblastoma cell differentiation 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Wnt1 has recently been proposed to mediate the timing of neurogenesis in the midbrain by driving Fgf8 expression at the boundary and gradually suppressing it away from the boundary by inducing Sprouty expression so that Fgf dependent her5 also recedes (Dyer et al, 2014 ). Wnt1 may also function to promote neural stem cell identity in the dorsal midbrain and MHB (Miyake et al, 2012 ; Lin and Lee, 2016 ), possibly regulated by Fgf3/8-dependent Fgf22 signaling (Miyake and Itoh, 2013 ) and may contribute to shaping the MH by regulating the cytoskeleton during axon guidance (Ciani and Salinas, 2005 ). In the hindbrain, differentiation of unique tegmentum nuclei identities happens in spatiotemporal waves emanating from the upper rhombic lip.…”
Section: Midbrain Hindbrain Domain Morphogenesis and Patterningmentioning
confidence: 99%
“…However, both Wnt and Fgf signaling can inhibit GSK3, the primary component of the destruction complex that modulates beta-catenin levels (Dailey et al, 2005 ). Thus, a careful balance of Wnt/Fgf signaling may affect Wnt target genes during MH development such as snail (Yook et al, 2005 ) and twist (Klymkowsky et al, 2010 ), zic2a/5 (Nyholm et al, 2009 ), cyclinD (Megason and McMahon, 2002 ), stmn4 (Lin and Lee, 2016 ), and dpagt1 (Varelas et al, 2014 ), genes known to affect cell proliferation, dorsolateral hinge-point (DLHP) formation, and adhesion. Classical Fgf signaling may also be important in Bergman glial fate specification in the cerebellum (Meier et al, 2014 ).…”
Section: Morphogenetic Roles For Wnt and Fgf Signaling During Constrimentioning
confidence: 99%